Nonlinear control study on aircraft engine using a generalized minimum variance approach. (September 2016) - Yu, Bing; Gao, Yang; Wang, Jiqiang
With the requirements of the advanced propulsion systems for aircraft control performance increasing, it has attracted the attention to design more efficient controller that is based on the nonlinear model over the flight envelope directly. A nonlinear aircraft engine control method based on generalized minimum variance approach is studied. A nonlinear autoregressive with extra input aircraft engine model for a certain turbofan engine is built and is chosen as the control plant in this study. Then, a controller is designed for the identification model based on the nonlinear generalized minimum variance theory. And simulation results manifest the controller to satisfy the requirements of the tracking with the transient process and the regulation with the steady process.